Examination of Muslim Zilennial Consumers’ Intentions to Eat at Popular Restaurants : Do Islamic Values Matter? - Mia Sari (SMART Insight, 2022)
In the current onslaught of digitalization era, understanding the intentions and preferences of Zilennial consumers towards popular restaurants is crucial for researchers and business practitioners alike. Hence, this research aims to examine Muslim consumers' intentions to dine at